Architect of bold European open-access plan heads to Washington to garner US support. (11th October 2018) - Else, Holly
Robert-Jan Smits takes Plan S to the White House to seek support from US funders and policymakers. Robert-Jan Smits takes Plan S to the White House and says he is in the United States for 'business not chit-chat'.